THE INFLUENCE OF OPENING ON NATURAL LIGHTING AND CONVENTION IN JOYOBOYO TERMINAL SURABAYA - Rachmalia, Indah; Romadhoni, Nur; Tarra, Bintang Mahendra; Arfianti, Ami (ADBE, 2023)
Joyoboyo Terminal is a public facility that accommodates public transport in the city of Surabaya. In addition to serving public transportation activities, this terminal is also a parking area for tourists who want to do activities in Surabaya Zoo. The city of Surabaya itself is known as a city with an extreme average temperature ranging from 24°C to 34°C. As a public building with high vehicle activity in it, the percentage of pollution generated by motor vehicles inside the Joyoboyo Terminal tends to be high coupled with the city temperature of Surabaya which belongs very hot. Then in its design, Joyoboyo Terminal applied the concept of green building by applying openings on almost every side by placing plants in the facade area on the northern and southern sides. With this opening, the air circulation inside the building is expected to be smooth so that it can produce comfort in the space. The application of openings and plants has already met variable standards according to the Green Building Council Indonesia. Using the method of research descriptive analysis is expected to be able to know the problems in the building based on data from field observations and literature studies, as well as to identify the role and influence of openings for heating and natural lighting on patterns of activity and comfort within the building. Through this research is also expected to be a case study in both criticizing a project object and critical in the planning process itself.